International directory of new and renewable information sources and research centres (UNESCO ParisFR, 1986)
For each country six kinds of organizations are listed viz. national government organizations, information resources, research centres, professional and trade associations, and publications. Includes an organization index which lists all national and international organizations, parent and affiliated, alphabetically. A country listing is also provided. An alphabetical subject index arranged by technical areas of interests contains lists of countries with the relevant item numbers. A publication index contains databases, directories and journals.
Bibliography: p. 660-661